IMPLEMENTASI KEGIATAN PROGRAM KREATIVITAS MAHASISWA BIDANG KEWIRAUSAHAAN (PKM-K) “BLACK HOT (DODOL JAHE)” - Sahbana, Yudhi Aulia; Pratiwi, Ega; Syafitri, Ema; Sari, Purwita (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
The study aims to describe business management including the various innovations carried out in the implementation of one of the 2020 Student Creativity Program in Entrepreneurship (PKM-K) activities that have been carried out virtually. In general, PKM-K activities aim to foster students' understanding and skills in producing unique communities and pioneering profit-oriented entrepreneurship. PKM-K activities are funded by Dikti, namely the